The effect of goji berry consumption on weight loss in boxers - Samar, Ezgi; Beyleroglu, Malik (Progress in Nutrition, 2020)
Study Objectives:The aim of this study was to examine whether goji berry consumption has an effect on weight loss in boxers. 24 licensed boxing athletes participated in the study. Methods:Athletes were divided into four groups (Group 1: Control group; Group 2: consuming Goji Berry; Group 3: Training group; Group 4: Goji Berry consuming + Training group) by simple random sampling method. Measurements were carried out two times as pre-test and post-test within the scope of the 6-week training program (3 training per week and 75 minutes for each training). The athletes, who subjected to a diet program while spending their periods in clubs, were given goji berry fruit once a day at the same time in the form of 30 g dried fruit. Descriptive statistics (mean and standard deviation) were calculated in the analysis of the data. The percentage of changing body composition of boxing athletes during the test was calculated with the formula “%Δ= (Post-Test – Pre-Test)/Pre-Test × 100”.The difference between the body weight percentage changes of the groups was compared with the One-Way ANOVA and Two-Way repeated measures ANOVA was used in the analysis of the variables measured repeatedly (pre-test and post-test) between the groups. The significance level was set at p<0,05 and p<0,01.Results:According to the findings of the research, it was determined that the highest decrease in body mass index, fat mass and visceral fat ratio, and the highest increase in free-fat mass and basal metabolic rate per kg were in the Goji Berry consuming + Training group. Conclusion:As a result, athletes interested in sports included weight category can use goji berry fruit for body weight control and reduction, which can help them achieve body weight loss and/or control.